Advance in the clinical studies on Traditional Chinese Medicine hot ironing compress therapy (中药热熨敷技术的临床研究进展) - DENG Jianhua (邓建华); LI Yuxin (李玉欣); LIU Sichun (刘司春); LI Xiuli (李秀丽); LI Yuanyuan (李媛媛); TANG Ling (唐玲) (中西医结合护理)
Traditional Chinese Medicine (TCM) hot ironing compress therapy is a common external intervention of Traditional Chinese Medicine nursing techniques. It has been widely used in clinical settings as its advantages, such as less pain, better effective, easier to practice and so on. This paper summarized the source, components and clinical application on TCM hot ironing compress in the literature. (中药热熨敷属药熨法, 是现代中医护理技术中比较常用的一种中医外治法, 因其痛苦小、疗效佳、操作简便, 临床应用较广。本文结合文献对中药热熨敷源流及概述、作用原理、药物组成及临床应用情况作一综述。)